2017
DOI: 10.1063/1.4986085
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of laser-ablation plumes and induced shock waves in low-pressure gas

Abstract: We investigated correlations between the temporal evolutions of shock waves and plasma plumes generated by pulsed laser ablation of an aluminum target under various background gas pressures. Using a probe-beam deflection technique with a high-gain amplifier, we succeeded in detecting relatively weak shock waves in a thin gas with a pressure down to 200 Pa, which is considered to be a suitable condition for cluster formation. The behavior of the expanding plume was also observed using a high-speed framing camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…When the focal point is 5 mm below the plate, the initial plasma is generated at the surface of the target by LA. The expansion of the plasma is not significant, which is consistent with the result of Chiba et al [45].…”
Section: Laser-induced Gas Breakdown and Laser Ablation In Quiescent Airsupporting
confidence: 92%
“…When the focal point is 5 mm below the plate, the initial plasma is generated at the surface of the target by LA. The expansion of the plasma is not significant, which is consistent with the result of Chiba et al [45].…”
Section: Laser-induced Gas Breakdown and Laser Ablation In Quiescent Airsupporting
confidence: 92%
“…The creation of the laser-induced plasma is accompanied by a shock wave, which can be described as an N-wave acoustic pulse 46 primarily, a short, approximately 300-μs-long compression/rarefaction acoustic signal. This signal is followed by echoes on nearby rocks and the rover structure, plus diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…213,214 Generally, larger shockwave propagation distances and velocities are routinely observed for atmospheric conditions consisting of lower gas pressures and densities. 54,200,[215][216][217] It has also been shown that shockwave velocities increase for decreasing irradiation wavelengths used during LA. 218 Furthermore, higher laser fluences produce stronger shockwaves with larger propagation velocities.…”
Section: Laser Ablation Plasma Chemistrymentioning
confidence: 99%